Charging ahead on the transition to electric vehicles with standard 120 V wall outlets. (1st November 2015) - Saxena, Samveg; MacDonald, Jason; Moura, Scott
Highlights: Commercially available EVs satisfy the daily travel needs of over 85% of US drivers. Charging EVs with standard 120 V outlets at home only is enough for most drivers. With EVs over 77% of drivers will have over 60 km buffer range for unexpected trips. EVs meet driver needs even with terrain, high ancillary losses, and capacity fade. 120 V outlets in more locations is more useful than fast chargers in fewer locations. Abstract: Electrification of transportation is needed soon and at significant scale to meet climate goals, but electric vehicle adoption has been slow and there has been little systematic analysis to show that today's electric vehicles meet the needs of drivers. We apply detailed physics-based models of electric vehicles with data on how drivers use their cars on a daily basis. We show that the energy storage limits of today's electric vehicles are outweighed by their high efficiency and the fact that driving in the United States seldom exceeds 100 km of daily travel. When accounting for these factors, we show that the normal daily travel of 85–89% of drivers in the United States can be satisfied with electric vehicles charging with standard 120 V wall outlets at home only. Further, we show that 77–79% of drivers on their normal daily driving will have over 60 km of buffer range for unexpected trips. We quantify the sensitivities to terrain, high ancillary power draw, and battery degradation and show that an extreme case with all trips on a 3% uphill grade still shows the daily travel of 70% of drivers being satisfied with electric vehicles. These findings show that today's electric vehicles can satisfy the daily driving needs of a significant majority of drivers using only 120 V wall outlets that are already the standard across the United States.